Copper molybdenum sulfide: A novel pseudocapacitive electrode material for electrochemical energy storage device. (5th July 2018) - Sahoo, Surjit; Krishnamoorthy, Karthikeyan; Pazhamalai, Parthiban; Mariappan, Vimal Kumar; Kim, Sang -Jae
Abstract: The ever-growing demand for energy storage devices necessitates the development of novel energy storage materials with high performance. In this work, copper molybdenum sulfide (Cu2 MoS4 ) nanostructures were prepared via a one-pot hydrothermal method and examined as an advanced electrode material for supercapacitor. Physico-chemical characterizations such as X-ray diffraction, laser Raman, field emission scanning electron microscope with elemental mapping, and X-ray photoelectron spectroscopy analyses revealed the formation of I-phase Cu2 MoS4 . Electrochemical analysis using cyclic voltammetry (CV), charge-discharge (CD) and electrochemical impedance spectroscopy (EIS) showed the pseudocapacitive nature of charge-storage via ion intercalation/de-intercalation occurring in the Cu2 MoS4 electrode. The Cu2 MoS4 electrode delivered a specific capacitance of 127 F g −1 obtained from the CD measured using a constant current density of 1.5 mA cm −2 . Further, Cu2 MoS4 symmetric supercapacitor (SSC) device delivered a specific capacitance of 28.25 F g −1 at a current density of 0.25 mA cm −2 with excellent rate capability. The device acquired high energy and power density of 3.92 Wh kg −1 and 1250 W kg −1, respectively. The Nyquist and Bode analysis further confirmed the pseudocapacitive nature of Cu2 MoS4 electrodes. The experimental results indicate the potential application of Cu2 MoS4 nanostructures as a novel electrode material for energy storage devices. Graphical abstract: We have effectively prepared Cu2 MoS4 nanostructures via a facile hydrothermal approach and investigated their electrochemical performance in three electrode system and SSC device in the aqueous Na2 SO4 electrolyte. Electrochemical studies revealed the pseudocapacitive nature of charge-storage via ion intercalation/de-intercalation occurring in the Cu2 MoS4 electrode. The Cu2 MoS4 SSC device delivered a high specific capacitance of 28.25 F g −1 obtained at a current density of 0.25 mA cm −2 with excellent cyclic stability over 3000 charge-discharge cycles. Highlights: Cu2 MoS4 nanostructures were prepared using a facile hydrothermal route. XRD analysis revealed the formation of I-phase Cu2 MoS4 nanostructures. Electrochemical studies revealed the pseudocapacitive nature of Cu2 MoS4 electrode. Cu2 MoS4 SSC device delivered a specific capacitance of 28.25 F g −1 at 0.25 mA cm −2 .